Performance of Wavelet-based Multiresolution Motion Estimation for Inbetweeningin Old Animated Films - Dwi Ratna Sulistyaningrum; Mochamad Hariadi; Mauridhi Hery Purnomo (Journal of ICT Research and Applications, 2012)
This  paper  investigates the  performance  of  wavelet-based multiresolution  motion  estimation (MRME)  for  inbetweening  in  old  animated films  using  three different  MRME  schemes.  The  three  schemes  are:  coarse-to fine with a wavelet-based MRME, one of Zhang's MRMEs, and an MRME in the spatial domain.  In order to make a performance comparison of these MRME  schemes,  two  video  sequences were  used  for  a  simulation.  The  experimental results  show  that  the  coarse-to-fine  method  performed  better  than  Zhang's  MRME  and  the  MRME in the spatial domain. The evaluation results  on block size 9x9 indicate that the coarse-to-fine method had an average peak signal-to-noise ratio (PSNR) of  23.48 dB for the first sequence and 29.84 for the second sequence.